The barriers to the involvement of children in the consent to their own treatment: A critical review - Harriet, Gray (2014)
AbstractAbstractAbstractAbstractAbstractAbstractAbstractAbstract (Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298)(Word Count: 298) This critical review aims to identify and evaluate the factors impacting children’s involvement in giving consent. The UK Gillick Case Law and the Convention on the Rights of the Child emphasise children’s rights within healthcare, both to participate in and consent to treatment. In order to give consent children must demonstrate their competence. Yet in practice, children’s competence is not always assessed and therefore children do not participate as they should. Consent with children is complex, involving the views of the child, their parents and health professionals. Within each of these, several key influences in gaining consent from children have been identified. These include their perception of children and therefore their role in healthcare decisions, along with knowledge, experience and culture. There is an evident need for professionals to consider the individuality of children when gaining consent. Each child’s personal experience and cognition must be considered when assessing their competence. Considering the individuality of children, all children should therefore be involved in consent according to their level of competence. Consent is on a continuum and children should be assessed, and then involved according to their level. Also, nurses must acknowledge their role in consent; consent is not just required for surgical procedures but for every invasion of personal space. Concluding, it is recommended that: clear and effective guidance is written, regular interprofessional training is initiated both pre and post registration, and the role of champions in consent is created. Such champions could foster long-term organisational change, enabling the NHS to become a place where children’s views are heard. Finally, research is recommended addressing nurses’ knowledge and attitudes towards consent, methods of engaging children in consent such as through play and child-friendly consent forms, and the role of champions in consent.